United States of America policy in the region of the Persian Gulf - Слободян Н. (Видавничо-поліграфічний центр "Київський університет", 2007)
The article is devoted the analysis of United States of America policy in the region of the Persian Gulf (period of 1992-2006 years). Analyzed forms and basic directions of foreign-policy strategy of the USA, and also facilities of its realization to the countries of the Persian Gulf.

Проаналізовано політику Сполучених Штатів Америки в регіоні Перської затоки в період 1992–2006 рр. З'ясовано форми та основні напрями зовнішньополітичної стратегії США, а також засоби її реалізації щодо країн Перської затоки.
Політика США в Перській затоці